ESSENTIAL CHARACTERISTICS OF EDUCATION AND PSYCHOLOGICAL COMPETENCE AND FORMATION OF FUTURE LOGIC THERAPISTS - Khonbabayeva Madinabonu Asqarjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article is aimed at explaining theoretical information about competence. Also, the importance of psychological knowledge in the pedagogical process and the qualities of competence are briefly covered.